LemPhos – New P-Chiral Phospholene Core Based Ligand - Włodarczyk, Adam; Ponikiewski, Łukasz (Synthesis, 2024)
Synthesis and modifications of new chiral phospholene-based scaffolds are described. The construction of base molecules was accomplished via McCormack synthesis. Separation of single P-epimers was accomplished with column chromatography on silica gel.
Keywords: phosphines; phospholenes; ligands; nopadiene; asymmetric reactions